The Ongoing Challenge: American Workers and Unions - Russell, Jason (Labour / Le Travail, 2008)
The article reviews several books on American workers and unions including "Hard Work: Remaking the American Labor Movement," by Rick Fantasia and Kim Voss, "Demanding Work: The Paradox of Job Quality in the Affluent Economy," by Francis Green, and "Freedom Is Not Enough: The Opening of the American Workplace," by Nancy MacLean.
Keywords: BOOKS – Reviews; DEMANDING Work: The Paradox of Job Quality in the Affluent Economy (Book); FANTASIA; Rick; FREEDOM Is Not Enough: The Opening of the American Workplace (Book); GREEN; Francis; HARD Work: Remaking the American Labor Movement (Book); MACLEAN; Nancy; Nonfiction; VOSS; Kim